Avaliação das técnicas de dispersão mecânica e ultrassônica de nanotubos de carbono de paredes múltiplas em resina epóxi - Susin, Samuel Brando (My University, 2014)
In this study nanotubes/epoxy composites were produced in order to evaluate which of the two studied techniques would result in a better degree of dispersion and unentanglement of carbon nanotubes in epoxy resin. The analized techniques were mechanical dispersion with a DRAIS mixer and sonication. The nanocomposites obtained were evaluated by scanning and transmission electron microscopy. Also the activation energys of the systems were calculated from differential scanning calorimetry data. The results obtained indicates that the degree of dispersion for the mechanical processing method seems better than that of sonication. It could be due to the interference of nanotubes on the crosslink network formation, which resulted on the increase of cure reaction activation energy for the mechanically dispersed samples. However, the sonicated samples activation energy decreased indicating a less dispersed and more agglomerated state.
Com o intuito de identificar dentre os métodos de dispersão mecânica e por sonificação, qual apresentaria melhor desempenho na promoção do desemaranhamento e dispersão de nanotubos de carbono em resina epóxi, nesse trabalho foram elaborados compósitos nanotubos/epóxi. Os nanocompósitos obtidos foram submetidos a avaliações de microscopia eletrônica de varredura e de transmissão, além de investigações na cinética de cura a partir de dados de calorimetria diferencial exploratória. Os resultados encontrados indicam que o nível de dispersão das amostras do processo de dispersão mecânica foi melhor quando comparado com as amostras sonificadas. Isso devido principalmente a interferência dos nanotubos dispersos na formação de ligações cruzadas. O que levou ao aumento dos valores de energia de ativação da reação de cura nas amostras de dispersão mecânica em relação a resina pura, enquanto nas amostras sonificadas houve uma queda nesses valores, indicando um estado mais aglomerado dos nanotubos.
Keywords: Engenharia de materiais e metalúrgica; Resina epóxi; Nanotubos; Polímeros; Nanotecnologia; Materiais; Epoxy resins; Nanotubes; Polymers; Nanotechnology; Materials